PRINSIP AKUNTANSI ORGANISASI NIR LABA DAN PERANCANGAN SISTEM AKUNTANSI RUMAH SAKIT DENGAN STRATEGI CANNED SOFTWARE - SUGIARTO PRAJITNO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
This study discusses and examines two important parts of non-profit organizations accounting principles and strategies for developing a reliable accounting system. A thing researched specifically is about the application of accounting principles non-profit organization in hospital. Besides the issue of the principle of accounting information systems development strategy should produce a variety of information (financial statements) are needed by the users. There are significant differences between the accounting principles of non-profit organizations with a commercial venture. The principal difference is the financial statement item is a report that activity in a commercial venture called the income statement. The essential thing again is on its established objectives in the organization. This study uses the approach to the study of literature and data processing technology that will be used. Literature study was done by using a variety of literature and accounting standards on the issues of non-profit organizations, especially hospitals. Software that is used in the design of information systems is MYOB Accounting. The data used are fictitious data. This is the case of fictitious data and transactions that describe how the operational and reporting/ accountability of non-profit organization's activities in the accounting period. This study only emphasizes the journalizing logic that helps the residents learn to understand the logic of debiting and crediting. In addition, the learners and users of accounting software will gain knowledge of accounting principles and the use of accounting data processing technology in a practical.